B cell depletion in treating primary biliary cirrhosis: Pros and cons - Yin, Yu-Feng (Baishideng Publishing Group Co., Limited, 2012)
Primary biliary cirrhosis (PBC) is a progressive autoimmune liver disease of unknown etiology that affects almost exclusively women. Ursodeoxycholic acid (UDCA) is currently the only approved drug by Food and Drug Administration for patients with PBC. Although the precise pathogenesis of PBC remains unclear, it has been postulated that many cell populations, including B cells, are involved in the ongoing inflammatory process, which implicates, not surprisingly, a potential therapeutic target of depleting B cell to treat this disorder. Rituximab is a chimeric anti-CD20 monoclonal antibody that has been approved for the treatment of lymphoma and some autoimmune diseases such as rheumatoid arthritis. Whether it is effective in the treatment of PBC has not been evaluated. Recently, Tsuda et al([1]) demonstrated that B cell depletion with rituximab significantly reduced the number of anti-mitochondrial antibodies (AMA)-producing B cells, AMA titers, the plasma levels of immunoglobulins (IgA, IgM and IgG) as well as serum alkaline phosphatase, and it was well tolerated by all the treated patients with no serious adverse events. This observation provides a novel treatment option for the patients with PBC who have incomplete response to UDCA.